2016
DOI: 10.7759/cureus.902
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Mean Red Cell Distribution Width in Hypertensive Patients

Abstract: PurposeRed cell distribution width (RDW), expressed in femtoliters (fl), is a measure of the variation in the size of circulating erythrocytes and is often expressed as a direct measurement of the width of the distribution. We aim to observe the mean value of red cell distribution width (RDW) in hypertensive patients. Increased RDW can be used as a tool for early diagnosis, as an inflammatory marker, and a mortality indicator in hypertensive patients due to its close relation to inflammation.Materials and meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 30 publications
(28 reference statements)
1
20
0
Order By: Relevance
“…Inflammation not only disrupts the survival of erythrocytes but also deforms red block cell membranes [ 22 , 23 ]. Taken together, increased systemic inflammation is the major theorized mechanism that results in an increase in RDW [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation not only disrupts the survival of erythrocytes but also deforms red block cell membranes [ 22 , 23 ]. Taken together, increased systemic inflammation is the major theorized mechanism that results in an increase in RDW [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…18 Bilal et al evaluated 100 hypertensive patients and found that most of these patients had an increased level of RDW. 64 Similarly, Ozcan et al validated the association between RDW and hypertension in 247 patients with essential hypertension and found that RDW is significantly higher in patients with non-dipper hypertension compared with the dipper hypertensive patients. 65 Furthermore, it has been demonstrated that nebivolol, an anti-hypertensive drug, decreased RDW in new essential hypertensive patients, supporting the hypothesis that RDW could be used in clinic as a novel biomarker for evaluating the hypertension-associated complications in cardiovascular disease.…”
Section: Hypertensive Heart Disease and Rdwmentioning
confidence: 96%
“…Moreover, it has been demonstrated that elevated RDW is strongly associated with systolic and diastolic blood pressures . Bilal et al evaluated 100 hypertensive patients and found that most of these patients had an increased level of RDW . Similarly, Ozcan et al validated the association between RDW and hypertension in 247 patients with essential hypertension and found that RDW is significantly higher in patients with non‐dipper hypertension compared with the dipper hypertensive patients .…”
Section: Hypertensive Heart Disease and Rdwmentioning
confidence: 99%
“…Increased RDW has been also observed to co-exist with multiple cardiovascular disorders, such as hypertension (Bilal et al 2016), atrial fibrillation (Shao et al 2018) and heart failure (Lippi et al 2018). However, little is known regarding the significance of this association.…”
Section: Introductionmentioning
confidence: 99%